INTEGRATION OF LOCAL LITERATURE VALUES IN THE IMPLEMENTATION OF 2013 CURRICULUM - Sahlan, S; Amiruddin, A (PPs UNJ, 2016)
The 2013 Curriculum describes the core competencies (KI) into four aspects of competence, namely (1) spiritual, (2) social, (3) cognitive, and (4) psychomotor aspects. The spiritual and the social aspects of learning materials development is done in an integrated manner, namely through the development of cognitive aspects (knowledge) of KI 3, and psychomotor aspects (skills) of KI 4. Therefore, the integration literature values in the areas of learning may be one of the teachers choices. The objective is to make the learning materials comply with students schemata or insight. Based on the content analysis that has been done in some local literatures both in folklores and poetries, local literature contains a lot of character values. Thus, local literatures may contribute to the implementation of 2013 Curriculum, so that teachers can integrate them in the development of learning. Local literatures in Southeast Sulawesi such as; Oheo Folklore for Tolaki people, Wandoke-Doke te Lakolo-kolopua Folklore for Muna People, or Wandiu-Diu Folklore for Buton people contains a lot of character values, both in terms of spiritual and social values. Folk Songs such as Kabanti, Kantola also has similar values in the society; they have humanistic, moral, mutual assistance, hard work, discipline, and struggle values. Spiritual values in the local literatures, among others are, belief in the greatness of Allah SWT, confidence in Gods grace in all its activities, and surrender to Allah. Character values on learning in the implementation of the 2013 Curriculum, among others are; discipline, hard work, honesty, responsibility, working together, affection, and respect. Thus, the values of the local literature or local culture is highly relevant to the values of character education, and therefore local literature values can be integrated in the learning area designed by teachers in the implementation of 2013 Curriculum, especially in developing KI 1 and KI 2 in learning.